Correlation Between Platelet Distribution Width and Mean Platelet Volume with Hematocrit in Dengue Hemorrhagic Fever Patients at Prof. Dr. Chairuddin Panusunan Lubis Hospital Universitas Sumatera Utara - Dewi Fortuna Chairiya; Almaycano Ginting; Aida Fitri; Bastian Lubis (Sumatera Medical Journal, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is a dengue virus (DENV) infection through the bite of an infected mosquito that manifests clinically in the form of high fever, headache, muscle pain, nausea, and rash. Research shows that several regions in Southeast Asia, including Indonesia, will experience an increase in the incidence of dengue infection in 2050 and 2080. Objective: This study aims to determine the correlation between platelet distribution width (PDW) and mean platelet volume (MPV) with hematocrit (Hct) in patients with Dengue Hemorrhagic Fever (DHF) at the Prof. Dr. Chairuddin Panusunan Lubis Teaching Hospital, Universitas Sumatera Utara. Methods: This study was conducted with a cross-sectional design. The subjects of this study were 142 DHF patients aged > 17 years obtained from medical record data at the Prof. Dr. Chairuddin Panusunan Lubis Hospital, Universitas Sumatera Utara. Statistical analysis using the Pearson Correlation Test. Results: In 142 study subjects, it was found that the majority of patients were in the age range of 18-39 years (83,8%) and were male (51.4%). The majority of patients had normal PDW values ​​(85.2%), normal MPV values ​​(91.5%), and normal hematocrit values ​​(59.1%). Conclusion: No significant correlation was found between PDW and MPV with Hct in DHF patients.